Preparing for Climate Change in Agricultural Drylands with a Focus on West Africa - Dietz, Ton (Annals of Arid Zone, 2016)
Climate changc will have impacts all over the world, positive and negative. hut these impacts are not evenly spread over the world. It can be expected that many of the world's drylands will experience severe livelihood shocks as a result of climate change in thc coming decades, and the agricultural drylands in West Africa are often mentioned as the ones that will be hit most by increased rainfall volatility (droughts. hut also floods). This paper uses the approach and the results of a major Dutch-West African research project (the Impact of Climate Change in Drylands, with a focus on West Africa: 1998-2004). and puts these results in perspective of other, and more recent research findings.